The biological effect of a combination of platelet lysate and amniotic membrane in buccal epithelium culture - E. V. Chentsova; N. V. Borovkova; P. V. Makarov; D. A. Bozhenko; I. N. Ponomarev; M. V. Storozheva; M. S. Makarov (Российский офтальмологический журнал, 2022)
Purpose: To study the biological effect of a combination of platelet lysate and amniotic membrane, preserved by various techniques, on human buccal epithelium culture. Materials and methods. Human amnion transplants were preserved using 3 methods: silicate drying, lyophilization, cryopreservation. The blood of healthy volunteers was used as a source of platelets. Platelet-rich plasma (PRP) with a platelet content over 1000 thousand/mcl and more was isolated from the donors blood, frozen at -80 °С and defrosted at 0–4 °С to prepare platelet lysate. Growth-stimulating effect of the amnion transplants was studied in different groups: control group 1 — without amnion and without PRP lysate; control group 2 — PRP lysate without amnion; experimental group 1 — amnion without PRP lysate; experimental group 2 — amnion samples combined with PRP lysate. The study was carried out on the example of human buccal epithelium culture of 3–5 passages. The dynamics of cell growth was evaluated after 1, 2 and 3 days from the moment of seeding. The number of cells and their viability were evaluated using original methods based on vital cell staining and their examination in a fluorescent microscope. Results. All samples of preserved amnions were non-toxic and did not damage the structural and functional characteristics of the buccal epithelium. On the other hand, the use of amnion without PRP lysate did not have a growth-stimulating effect on cells. Among the amnion samples combined with PRP lysate, the combination of lyophilized amnion and PRP lysate was the most effective during the entire study period. Conclusions. Silicate drying, lyophilization and cryopreservation of the amniotic membrane makes it possible to obtain biocompatible and non-toxic transplants, based on human amnion. Lyophilized amnions are the most optimal for saturating PRP lysate. The combination of lyophilized amnion and PRP lysate stimulates cell growth in vitro without violating their structural integrity.